Perioperative Morbidity and Mortality in Octogenarians With Ovarian Cancer. Issue 6 (1st July 2013) - Walters, Christen L.; Schneider, Kellie E.; Whitworth, Jenny M.; Fauci, Janelle M.; Smith, Haller J.; Barnes, Mack N.; Straughn, J. Michael
Abstract : Background: The decision to choose surgical cytoreduction in patients with newly diagnosed ovarian cancer may be influenced by their age. We compared perioperative morbidity and mortality of octogenarians compared with younger patients undergoing surgical cytoreduction. Methods: A retrospective chart review identified patients who underwent primary surgical cytoreduction for ovarian cancer between January 2005 and December 2009. Patients were divided into 2 cohorts: younger than 80 years and 80 years or older (octogenarian). Patient demographics, surgical procedures, 30-day readmission, length of stay, 30-day mortality rates, and chemotherapy administration were examined. Student t test and χ 2 test were used to evaluate statistical significance. Results: Three hundred eighty-four patients who underwent surgical cytoreduction for ovarian cancer were identified. Three hundred fifty-two patients (91.7%) were younger than 80 years, whereas 32 patients (8.3%) were 80 years or older. Two hundred thirty-six women (67.0%) in the younger cohort had optimal cytoreduction (<1 cm) compared with 17 women (53.1%) in the older cohort ( P = 0.12). Thirty-day readmission rates and postoperative complications were similar. More patients in the older cohort required preoperative admission for medical clearance ( P < 0.01). Mean length of stay was significantly longer in the older cohort (10.0 vs 7.5; P = 0.02). The number of patients who received adjuvant chemotherapy was significantly lower in the older cohort (71.9% vs 93.8%; P < 0.01). The 30-day mortality rate was significantly higher in the older cohort (18.8% vs 4.0%; P < 0.01). Conclusions: Although octogenarians with ovarian cancer have similar surgical complication rates as their younger counterparts, they require more medical clearance and have a longer hospital stay. Older patients are less likely to undergo chemotherapy and have a higher 30-day mortality rate than are younger patients.